Treatment Of Refractory Gold-Antimony Concentrates With The Recovery Of Senarmontite - D. Royston (Society for Mining, Metallurgy & Exploration, 2007)
Gold ores containing antimony suffer from poor recoveries of gold in cyanidation due to the impact of antimony on the cyanidation process. Techniques such as lowering the pH for cyanidation can improve gold recovery, nevertheless a limit can be reached where high cyanide consumption makes traditional processing uneconomic. The paper outlines a process for the pre-treatment of gold-antimony concentrates to remove the antimony resulting in a low-antimony content gold-bearing residue suitable for efficient treatment for gold recovery through cyanidation. This hydrometallurgical process produces a by-product credit of commercial grade antimony trioxide as Senarmontite that can significantly offset the cost of the pre-treatment.